2021
DOI: 10.1111/bjh.17561
|View full text |Cite
|
Sign up to set email alerts
|

Delta‐globin gene expression improves sickle cell disease in a humanised mouse model

Abstract: Summary Sickle cell disease (SCD) is a widespread genetic disease associated with severe disability and multi‐organ damage, resulting in a reduced life expectancy. None of the existing clinical treatments provide a solution for all patients. Gene therapy and fetal haemoglobin (HbF) reactivation through genetic approaches have obtained promising, but early, results in patients. Furthermore, the search for active molecules to increase HbF is still ongoing. The delta‐globin gene produces the delta‐globin of haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Previous transgenic studies have shown that insertion of KLF1 alone to the HBD promoter sequence is sufficient to drive expression of HBD 6,16 . However, these studies do not reflect the complex chromatin context and regulation at the β-like globin locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous transgenic studies have shown that insertion of KLF1 alone to the HBD promoter sequence is sufficient to drive expression of HBD 6,16 . However, these studies do not reflect the complex chromatin context and regulation at the β-like globin locus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using transgenic approaches have shown that inclusion of a KLF1 motif in the HBD promoter can drive exogenous expression of δ-globin 6,16,17 . However, these studies do not reflect the complex chromosomal context and extensive epigenetic regulation at the β-like globin cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal hemoglobin (HbF), which is the predominant hemoglobin expressed before birth, has anti-sickling properties and its re-expression is frequently pursued as a treatment for β-hemoglobinopathies Wienert et al, 2018 . While increasing HbF has shown to be clinically effective to combat SCD, studies have also validated the in vitro and in vivo anti-sickling abilities of δ-globin using a humanized mouse model of SCD Nagel et al, 1979 ; Poillon et al, 1993 ; Porcu et al, 2021 ; Waterman et al, 1979 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using transgenic approaches have shown that inclusion of a KLF1 motif in the HBD promoter can drive exogenous expression of δ-globin Porcu et al, 2021 ; Donze et al, 1996 ; Ristaldi et al, 1999 . However, these studies do not reflect the complex chromosomal context and extensive epigenetic regulation at the β-like globin cluster.…”
Section: Introductionmentioning
confidence: 99%
“… 32 A recent study has shown that δ-globin gene expression improves the SCD phenotype in a humanized mouse model. 33 These findings led us to believe that human δ-globin gene activation could represent an alternative genetic therapeutic approach to hemoglobinopathies.…”
Section: Introductionmentioning
confidence: 99%